Dinamika Pertumbuhan Kangkung Darat (Ipomoea reptans Poir) terhadap Pemberian Biostimulan Asam Amino dan NPK - Alamanda Katartika Fahri; Adawiah; Rizki Afriliyanti (Universitas Muhammadiyah Kotabumi, 2026)
Water spinach (Ipomoea reptans Poir.) is a short-duration leafy vegetable whose early growth and marketable biomass depend on efficient nutrient management. This study aimed to evaluate growth dynamics and production of water spinach following application of an amino acid biostimulant and NPK fertilizer. The experiment was conducted at the Integrated Field Laboratory, Faculty of Agriculture, Universitas Lampung, in February 2026 using a one-factor randomized block design with three treatments and nine replications: no fertilizer, amino acid biostimulant (2 mL/L), and NPK 16-16-16 (1 g/L), applied as root drenches at 7 and 14 days after planting. The tested concentrations were selected to compare an organic growth-stimulating input with a mineral macronutrient source during the short vegetative cycle. Plant height and leaf number were recorded at 7, 14, 21, 28, and 35 days after planting, and fresh weight was measured at harvest. Data were evaluated descriptively using means, standard deviations, and percentage increases over the control. At 7 days after planting, NPK and amino acid biostimulant produced plant heights 101.5% and 68.6% above the control, respectively. At 35 days after planting, NPK produced the highest fresh weight (742.13 ± 2.41 g), followed by the amino acid biostimulant (655.88 ± 2.36 g) and the control (485.51 ± 2.45 g); the amino acid treatment produced the highest leaf number (16 leaves). These results indicate that NPK supported greater final fresh biomass, whereas the amino acid biostimulant tended to support early vegetative growth and leaf formation.